Pharmacokinetics of Repeated Oral Dosing with Coenzyme Q10 in Cavalier King Charles Spaniels with Myxomatous Mitral Valve Disease - Liselotte B. Christiansen; Malene K. Morsing; Maria Josefine Reimann; Torben Martinussen; Zita Birlie; Anne Marie V. Schou-Pedersen; Jens Lykkesfeldt; Lisbeth H. Olsen (MDPI AG, 2020)
Coenzyme Q10 (Q10) is a mitochondrial cofactor and an antioxidant with the potential to combat oxidative stress in heart failure. This study aims to determine the pharmacokinetics of repeated oral dosing of Q10 in Cavalier King Charles Spaniels (CKCS) with spontaneous myxomatous mitral valve disease (MMVD) and to evaluate echocardiographic parameters, circulating cardiac biomarkers, and quality of life (QoL) after treatment. The study is a randomized, placebo-controlled, single-blinded crossover study. Nineteen CKCS with MMVD were randomized to receive 100 mg Q10 (ubiquinone) bi-daily for three weeks, then placebo (or in reverse order). Clinical examination, blood sampling, echocardiography, and QoL assessment were performed before and after each treatment phase. Q10 plasma concentrations were determined in plasma using a validated high-performance liquid chromatography method using electrochemical detection (HPLC-ECD). Eighteen CKCS were included in the analyses. Total plasma concentration of Q10 increased significantly (p < 0.0001) from baseline (median, 0.92 µg/mL; interquartile range (IQR), 0.70-1.26) to after treatment (median, 3.51 µg/mL; IQR, 2.30-6.88). Thirteen dogs reached the threshold of a total plasma Q10 concentration of ≥2.0 µg/mL. The average half-life (T1/2) of Q10 was 2.95 days (IQR, 1.75-4.02). No significant differences were observed in clinical MMVD severity, and the owner perceived QoL between Q10 and placebo treatment. The solubilized Q10 formulation was well-tolerated in the dogs. Individual variation in plasma concentrations was observed following oral treatment. A long-term placebo-controlled trial is warranted in dogs with MMVD to determine long-term efficacy on the clinical severity of MMVD.